Keefektifan Model Children Learning in Science (CLIS) Untuk Meningkatkan Keterampilan Berpikir Rasional Siswa - Marlina Marlina; Zainuddin Zainuddin; Syubhan An'nur (Berkala Ilmiah Pendidikan Fisika, 2013)
The low of rational thinking skills of students in learning physics models encourage researchers to carry out Children’s Learning in Science (CLIS). This study aims to determine how the effectiveness of learning by using the model CLIS. The specific aims of research describing: (1) the ability of the teacher to manage the model CLIS, (2) rational thinking skills of students, (3) classical completeness student learning outcomes after participating in learning, (4) students' response to the model CLIS. The study was designed and implemented using classroom action research. The subject of this study is researcher and lecturer, 2 observers and 33 students of grade XI RPL SMK 4 Banjarmasin. The technique uses test data collection, observation, questionnaires, and documentation. The results showed an increase in the ability of teachers to manage the model CLIS in cycle I, II, and III respectively by 77.78%, 86.67%, and 94.44% aspects of the rational thinking skills students in cycle I, II, and III in general has increased very well. An increase in mastery learning outcomes classical cycle I, II, and III respectively amounted to 87.87%, 96.97% and 96.97%, CLIS students' response to the model in general is quite good.